2019
DOI: 10.1002/jssc.201900733
|View full text |Cite
|
Sign up to set email alerts
|

A novel open‐tubular capillary electrochromatography using carboxymethyl‐β‐cyclodextrin functionalized gold nanoparticles as chiral stationary phase

Abstract: Enantioselective open tubular capillary electrochromatography with carboxymethyl‐β‐cyclodextrin conjugated gold nanoparticles as stationary phase was developed. This novel open tubular column was fabricated through layer‐by‐layer self‐assembly of gold nanoparticles on a 3‐mercaptopropyl‐trimethoxysilane‐modified fused‐silica capillary and subsequent surface functionalization of the gold nanoparticles through self‐assembly of 6‐mercapto‐β‐cyclodextrin. The 6‐mercapto‐β‐cyclodextrin was firstly synthesized and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
(25 reference statements)
0
15
0
Order By: Relevance
“…Their work was validated by separation of six amino acid enantiomers. Finally, Zhang et al reported in 2019 the development of chiral OT-CEC with a stationary phase of modified β-CDs conjugated to gold nanoparticles [236]. After optimizing the conditions, they showed the enantioselective separation of tramadol hydrochloride and zopiclone with high resolution.…”
Section: Chiral Open-tubular Cecmentioning
confidence: 99%
“…Their work was validated by separation of six amino acid enantiomers. Finally, Zhang et al reported in 2019 the development of chiral OT-CEC with a stationary phase of modified β-CDs conjugated to gold nanoparticles [236]. After optimizing the conditions, they showed the enantioselective separation of tramadol hydrochloride and zopiclone with high resolution.…”
Section: Chiral Open-tubular Cecmentioning
confidence: 99%
“…Nonetheless, although it is highly difficult to compare directly the separation resolution between different analytes and columns, the effectiveness of each strategy is evident whereby in optimised conditions (i. e. pH, buffer concentrations, applied voltages, selected analyte, etc.) the separation resolutions are often well above 2.0, sometimes reaching above 4.0 . Furthermore, within the vast majority of listed published articles, the authors frequently analyse the stability of prepared columns and techniques extensively, along with adjustments to the methods, including changes to the polarity and pH of the mobile phase, for more in‐depth analysis of interactions and enantioseparation.…”
Section: Cyclodextrin Functionalised Nanomaterials In Chiral Recognitionmentioning
confidence: 99%
“…Ji's group successfully prepared of β-cyclodextrin covalent organic framework modified chiral stationary phase for separation of six enantiomers [21]. Fang et al developed an OT-CEC column using carboxymethyl-βcyclodextrin functionalized gold nanoparticles as chiral stationary phase [22]. Li also prepared β-cyclodextrin functionalized periodic mesoporous organosilica open tubular capillary columns for separating amino acid enantiomer derivatives [23].…”
Section: Introductionmentioning
confidence: 99%
“…Fang et al. developed an OT‐CEC column using carboxymethyl‐β‐cyclodextrin functionalized gold nanoparticles as chiral stationary phase [22]. Li also prepared β‐cyclodextrin functionalized periodic mesoporous organosilica open tubular capillary columns for separating amino acid enantiomer derivatives [23].…”
Section: Introductionmentioning
confidence: 99%